Multi-Target Actions of Flavonoid Derivatives from Mesua ferrea Linn Flower against Alzheimer’s disease Pathogenesis - Plekratoke, Kusawadee; Waiwut, Pornthip; Yenjai, Chavi; Monthakantirat, Orawan; Takomthong, Pitchayakarn; Nualkaew, Natsajee; Awale, Suresh; Chulikhit, Yaowared; Daodee, Supawadee; Khamphukdee, Charinya; Boonyarat, Chantana (Biomedical Sciences and Clinical Medicine, 2023)
OBJECTIVE Kaempferol-3-O-rhamnoside (compound 1) and quercetin- 3-O-rhamnoside (compound 2), two flavonoids isolated from Mesua ferrea L. flowers, were examined for their activities related Alzheimer’s disease (AD) pathogenesis including antioxidant, acetylcholinesterase (AChE) inhibition, anti-beta amyloid (Aβ) aggregation and neuroprotection. METHODS The two flavonoids were isolated from M. ferrea L. flowers using the column chromatography technique. Both compounds were evaluated for their effects on AD pathogenesis, including antioxidant action by ABTS assay, AChE inhibition by Ellman’s method, and anti-Aβ aggregation by thioflavin T (ThT) assay and neuroprotection by cell base assay. To explain the mechanism of AChE inhibition and anti-Aβ aggregation, binding interactions between the test compounds and AChE and Aβ were studied in-silico. RESULTS Compounds 1 and 2 showed an ability to scavenge ABTS radicals, with IC50 values of 424.57±2.97 and 308.67±9.90 μM, respectively, and to inhibit AChE function with IC50 values of 769.23±6.23 and 520.64±5.94, respectively. ThT assay indicated that both compounds inhibited Aβ aggregation with IC50 values of 406.43±9.95 and 300.69 ±1.18 μM, respectively. The neuroprotection study revealed that the two flavonoids could reduce human neuroblastoma (SH-SY5Y) cell death induced by H2O2. The in-silico study showed that both compounds bound AChE at catalytic anionic and peripheral anionic sites. In addition, the test compounds prevented Aβ aggregation by interacting at the central hydrophobic core, the C-terminal hydrophobic region, and the important residues of Ile41. CONCLUSIONS Together, the results showed that kaempferol-3-O- rhamnoside and quercetin-3-O- rhamnoside exhibit multiple mechanisms of action that are involved in the pathogenesis of AD including antioxidant, AChE inhibition, anti-Aβ aggregation, and neuroprotection.